Ethnic minority staff and patients: a health service failure. (21st May 2019) - Kmietowicz, Zosia; Ladher, Navjoyt; Rao, Mala; Salway, Sarah; Abbasi, Kamran; Adebowale, Victor
Abstract : A call for papers for a special theme issue of The BMJ